PET-CT scan-based maximum standardized uptake value as a prognostic predictor in oropharynx squamous cell cancer. (2021) - Patel, Yamini; Srivastava, Shelly; Rana, Divyesh; Goel, Anil; Suryanarayana, K.; Saini, Surendra Kumar
Highlights: Prognostic importance of pretreatment SUVmax in head neck cancer patients was shown in some studies but it was never confirmed with large trials. Meta-analysis was also not confirmatory due to use of different PET based marker, heterogeneous population, evolution of staging over time and limited follow up. Staging of head neck cancers evolved over time based on outcome and also incorporated various morphological marker and advanced imaging. It seems that effect of PET-CT on staging is more pronounced than on prognosis. This study confirms with longer follow up that pre treatment SUVmax should not be used as prognostic marker and it is rather a surrogate for advanced group stage. Abstract: Introduction: Positron emission tomography with 2-deoxy-2-[fluorine-18]fluoro-D-glucose integrated with computed tomography (18F-FDG PET-CT) is clinically useful and extensively used in initial staging and follow-up of patients with head and neck squamous cell carcinoma (HNSCC). We studied the potential prognostic significance of primary tumor maximum standard uptake value (SUVmax) by 18F-FDG PET-CT in oropharyngeal cancer. Methods: Sixty patients with early and locally advanced histopathologically proven oropharyngeal squamous cell cancer were staged using FDG PET-CT at diagnosis. All patient received radiation therapy and concurrent chemotherapy (in stage III and IVA disease) and were assessed prospectively for treatment outcome. Groups were created based on stage and cut off for SUVmax. The association of SUVmax of primary tumour and stage with disease-free survival and overall survival was analyzed by univariate and multivariate statistics. Results: In univariate analysis, a primary tumour SUVmax of greater than 13.0 and advanced stage (IVA) predicted inferior disease-free survival (P=0.0241 and 0.0005, respectively) and overall survival (P=0.0510, toward significance and 0.0003, respectively). In proportional hazards analysis, stage was significant only when adjusted for primary SUVmax. Conclusion: SUVmax failed to demonstrate predictive significance in oropharyngeal cancer, and an increase in primary tumor uptake is possibly a direct effect of advanced disease and consequently increased metabolic activity and aggressiveness.